The mismatch in hierarchical diagnosis and treatment construction and related reasons: a qualitative analysis from ZX City, Hubei Province - Yuhui Ruan; Mingming Yu (Frontiers in Public Health)
BackgroundThere is a substantial gap between the objective of hierarchical diagnosis and treatment (HDT) construction and its actual effectiveness in resolving the problems of difficult and expensive access to medical treatment. Consequently, it has become essential to address these issues through research.ObjectivesThis study intends to examine the mismatch in China’s HDT construction and identify its underlying causes.MethodsGrounded theory was employed in this research. Open questions were designed through theoretical sampling and coding processes until theoretical saturation was achieved. A total of 52 participants, all doctors from different levels of medical institutions in ZX City, Hubei Province, China, with more than 3 years of experience, were recruited.ResultsThis study uncovers significant mismatches between residents’ “pursuit of high-quality medical care” and HDT’s requirement of “initial diagnosis at the grassroots level,” between the service supply capacity and the functional positioning of medical institutions in HDT, and between the policy environment and HDT’s construction needs, respectively. The primary reasons for these discrepancies are residents’ lack of confidence, improper allocation of health resources, and the absence of in-depth health policy reforms.ConclusionThis study recommends restoring residents’ confidence in the service provision of low-level medical institutions to achieve initial diagnosis at the grassroots level, establishing a positive health resource–allocation pyramid from lower to higher levels to enhance the service capacity of primary health care institutions, and adjusting the policy environment to address and reform deep-seated policy contradictions and rationalize the functional positioning and matching relationship of medical institutions at all levels in HDT.